1973
DOI: 10.1071/zo9730437
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive characteristics of wild native Australian Rattus (Rodentia : Muridae)

Abstract: Reproduction in field populations of the five species and 13 of 14 subspecies of native Australian Rattus is compared, using both materials personally collected and museum specimens. We have separated each subspecies into juvenile and adult categories, the dividing point reflecting the approximate size at which sexual maturity is reached. Occurrence of pregnancies and juveniles, treated monthly, permit estimates of time and length of seasonal breeding for each subspecies. Information on gonads and accessory se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
2

Year Published

1980
1980
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(42 citation statements)
references
References 23 publications
1
39
2
Order By: Relevance
“…The observations in this study on the wild-trapped rats confirm and extend previous studies that male bush rats are seasonal breeders (Warneke, 1971 ;Taylor & Homer, 1973;Kerr et al, 1980 (Lincoln & Peet, 1977) in which serum testosterone levels rose in parallel with an increase in testicular growth, as in this study, but were out of phase with LH levels which were declining at the same time. Lincoln & Peet (1977) Dalterio, 1978).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The observations in this study on the wild-trapped rats confirm and extend previous studies that male bush rats are seasonal breeders (Warneke, 1971 ;Taylor & Homer, 1973;Kerr et al, 1980 (Lincoln & Peet, 1977) in which serum testosterone levels rose in parallel with an increase in testicular growth, as in this study, but were out of phase with LH levels which were declining at the same time. Lincoln & Peet (1977) Dalterio, 1978).…”
Section: Discussionsupporting
confidence: 80%
“…Previous studies of wild populations of the Australian bush rat, Rattus fuscipes, have shown that the males of this species have a seasonal reproductive cycle (Warneke, 1971 ;Taylor & Homer, 1973). During the summer breeding season they exhibit complete spermatogenesis, while in the winter months the spermatogenic cycle is arrested at the primary spermatocyte step.…”
Section: Introductionmentioning
confidence: 99%
“…In both locations, the proportion of pregnant females is greatest from spring to autumn (October-May). In the laboratory, R. fuscipes breeds throughout the year (Taylor 1961;Taylor and Horner 1973).…”
Section: Determinants Of Reproductive Characteristicsmentioning
confidence: 99%
“…That variation was generated by annual variation in rainfall late in the wet season; the rats depend upon moist soil for burrowing to obtain corms and other food, and thus cease reproducing when the flood plain begins to dry out. Under favourable conditions in captivity, this species breeds year-round ( Taylor & Horner 1973). A causal link between annual climatic (rainfall) variation and the duration of rodent breeding is supported by the observation of synchronized across-year variation in the duration of rat breeding across widely separated flood plains (Williams & Newsome 1991).…”
Section: (D) When To Cease Reproduction?mentioning
confidence: 99%